Dendrochronological dating and provenance determination of a 19th century whaler in Patagonia (Puerto Madryn, Argentina) - Mundo, Ignacio Alberto; Murray, C.; Grosso, M.; Rao, M.P.; Cook, E. R.; Villalba, Ricardo (Dendrochronologia)
Dendrochronological methods have been widely used to determine the date of construction and provenance of shipwrecks. Despite a large number of shipwrecks, the application of dendroarchaeological techniques is relatively incipient in the coasts of South America. This paper presents the results of a dendroarchaeological study conducted at the shipwreck site “Bahía Galenses” (BG), located in the western sector of Golfo Nuevo, on the Patagonian coast of the South Atlantic Ocean. Based on previous archaeological research, two hypotheses were tested in this study. First, the wreck described in the BG 2 sub-site corresponds to a mid-19th-century whaler built in the northeastern US. Second, these remains correspond to the Dolphin, a northeastern American whaler built in Warren (Rhode Island) in 1850 and shipwrecked in the Atlantic coast of Patagonia in 1859. Using dendroarchaeological provenance methods and a novel approach based on the gridded North American Drought Atlas, we found highly significant correlations between the wreck's tree-ring width series and white oak and yellow pine tree-ring reference chronologies from the eastern US. The latest non-cutting dates obtained in this analysis correspond to the year 1849. To our knowledge, our study pioneered the use of dendrochronological methods for dating and establishing the provenance of a whaler's remains on the Atlantic coast of South America and encourages the feasibility for future dendroarchaeological research based on the large number of wooden shipwrecks that occurred in the region. Fil: Mundo, Ignacio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Murray, C. Secretaría de Cultura de la Nación. Dirección Nacional ...